Substrate-bound agrin induces expression of acetylcholine receptor epsilon-subunit gene in cultured mammalian muscle cells. - Jones, G (1996)
Expression of the epsilon-subunit gene of the acetylcholine receptor (AChR) by myonuclei located at the neuromuscular junction is precisely regulated during development. A key role in this regulation is played by the synaptic portion of the basal lamina, a structure that is also known to contain agrin, a component responsible for the formation of postsynaptic specializations. We tested whether agrin has a function in synaptic AChR gene expression. Synaptic basal lamina from native adult muscle and recombinant agrin bound to various substrates induced in cultured rat myotubes AChR clusters that were colocalized with epsilon-subunit mRNA. Estimation of transcript levels by Northern hybridization analysis of total RNA showed a significant increase when myotubes were grown on substrate impregnated with agrin, but were unchanged when agrin was applied in the medium. The effect was independent of the receptor aggregating activity of the agrin isoform used, and agrin acted, at least in part, at the level of epsilon-subunit gene transcription. These findings are consistent with a role of agrin in the regulation of AChR subunit gene expression at the neuromuscular junction, which would depend on its binding to the synaptic basal lamina.